2017
DOI: 10.1182/bloodadvances.2016004119
|View full text |Cite
|
Sign up to set email alerts
|

ATG vs thiotepa with busulfan and cyclophosphamide in matched-related bone marrow transplantation for thalassemia

Abstract: Key Points• In low-risk BMT for thalassemia, ATGBuCy seems as effective as Tt-BuCy in the prevention of rejection and may decrease transplant-related mortality. received ATG-BuCy. All patients were ,15 years and had no hepatomegaly (liver #2 cm from costal margin). Actuarial overall survival in the Tt-BuCy and ATG-BuCy groups was 87% and 94% and thalassemia-free survival was 80% and 85% at a median follow-up of 37 and 17 months, respectively, with no significant differences by log-rank statistics. Substituting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Bone marrow transplantation (BMT) is considered the gold standard for treating severe β-TM. 5 When compared with BMT without ATG, the outcomes after human leukocyte antigen-matched sibling donor transplantation, the results using an ATG-containing preparative regimen in this study were similar to or better than those reported previously. 6,7 Similarly, the hematopoietic reconstruction was consistent with or even better than previously published data.…”
Section: Discussionsupporting
confidence: 82%
“…Bone marrow transplantation (BMT) is considered the gold standard for treating severe β-TM. 5 When compared with BMT without ATG, the outcomes after human leukocyte antigen-matched sibling donor transplantation, the results using an ATG-containing preparative regimen in this study were similar to or better than those reported previously. 6,7 Similarly, the hematopoietic reconstruction was consistent with or even better than previously published data.…”
Section: Discussionsupporting
confidence: 82%
“…Our outcome analysis seems to suggest that ST versus FT HLA typing might be associated with sizable differences in events related to HLA disparities, particularly GVHD. The unexpected finding of the slight increase in rejection rates observed in the FT cohort might be related to small sample size or to a graft-enhancing effect of HLA disparity in the GVH direction related to early antithymocyte globulin timing (days -12 to -10) [10] sparing alloreactive donor lymphocytes infused with the marrow. Although this type of analysis has major limitations given its retrospective nature, it has the advantage of being focused on a relatively homogeneous group of patients with a single disease at risk for both rejection and GVHD.…”
Section: Discussionmentioning
confidence: 89%
“…All patients underwent transplantation between August 2013 and June 2016 after conditioning with a combination of rabbit anti-thymocyte globulin, busulfan, and cyclophosphamide followed by the infusion of freshly harvested granulocyte colony-stimulating factor-primed donor marrow on day 0. Rejection/GVHD prophylaxis consisted of cyclosporin A, methotrexate, and low-dose prednisone [10].…”
Section: Methodsmentioning
confidence: 99%
“…Identification of candidates suitable for transplantation led to 391 patients getting human leukocyte antigen-typed and prepared for bone marrow transplantation from these centers. In all, 43 were transplanted with overall survival of 93% and disease-free survival of 77% at a mean cost of US $13,000 per transplant, including pretransplant preparation and late complications [45,46]. For these patients, online software specific for bone marrow transplantation was used [47].…”
Section: Resultsmentioning
confidence: 99%